The dynamics of distinction in audiovisual consumption in São Paulo city - Mira, Maria Celeste; Castro, Ana Lucia de [UNESP]; Michetti, Miqueli (Univ Sao Carlos, Dept Sociology Federal, 2023)
In this paper we analyze the dynamics of distinction through audiovisual consumption among individuals, groups and classes in Sao Paulo city, Brazil. With reference to content extracted from six focus groups, carried out with different class fractions, defined by multiple variables - as Bourdieu teaches -, the text seeks to understand how certain practices, works, institutions and agents are mobilized to demarcate belongings, exclusions and hierarchies in the production of groups that are differently positioned in the social, symbolic and geographic space.
Keywords: Distinction; Social classes; Cultural practices; Consumption; Audiovi- sual